COMMON ERRORS OF CONNECTOR IN WRITING PARAGRAPH - Sari, Dian Permata (Linguists : Journal of Linguistics and Language Teaching, 2018)
Second year students of English department in IAIN Bengkulu were still faced a lot of difficulties in learning English. Most of them still have difficulties in understanding grammatical rules and because of their lack understanding of writing English especially in using connector. They were still unable to write a good paragraph, even the smaller unit like a sentence correctly. This research was a case study, the objective of the study were to find out the common error of connector, the dominant error of connector in students writing paragraph and To find out the factors that caused error of connector in students writing paragraph. The researcher used descriptive qualitative research design, it was used to get the description about connector by analyzing, interpreting, and concluding. In this case, the researcher aimed to find out about the common errors of connectors particularly in using coordinate, subordinate, and correlative connectors made by students in writing paragraph. The object of this research was the the fourth semester students of English department in IAIN Bengkulu in the academic year 2014/2015. 19 students were taken as the respondent by using purposeful random sampling. The data were collected by using students written paragraph and an interview, then the researcher interpreted all the data and found that the most common errors of the fourth semester students of English department on IAIN Bengkulu in their writing paragraph was coordinate connector and which was occurred 57,8 % from the total number of error. The errors of connectors were identified based on “Writing Academic English” book written by Oshima and Hoque. From the total number of error in this study, the researcher found that 21,05 % of error was stringy sentence, 26,31 % was unparalleled, 15,78 % was comma splice, and 36,84 % was miss function. So the dominant factor of connector error in writing paragraph that made by the fourth semester students of English department on IAIN Bengkulu was caused by miss function of connector. The result was relevant with the interview, where the students admitted that the factor of error in using connector was because  they has lack knowledge about connector and its functions. moreover the students were not taught specifically about connector by the teacher.